2023
DOI: 10.1136/archdischild-2023-325767
|View full text |Cite
|
Sign up to set email alerts
|

Perceived influence of commercial milk formula labelling on mothers’ feeding choices in Great Britain: a qualitative study

Abstract: ObjectiveTo understand how mothers use commercial milk formula (CMF) labels to inform their feeding choices and explore mothers’ understanding of differences between CMF products.DesignQualitative study with recruitment via social media. Online semistructured interviews, including a product mapping exercise and thematic analysis.ParticipantsMothers (n=25) using CMF for children <3 years living in Great Britain (GB).ResultsMothers were drawn to brands they recognised from years of exposure to CMF advertising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Further research has examined the impact of food package graphic design on consumers, with these studies showing the utility of graphic design for being a useful tool in communicating consumer benefits ( 47 ), that the positioning of packaging elements influences consumer attention ( 48 ), and that a relationship between packaging design and willingness to pay exists ( 49 ). Additionally, food pack design research has shown that consumers are able to process multiple packaging messages concurrently ( 47 ), that visual design cues are an important influence on consumer choices ( 10 , 50 , 51 ), and that brand and other visual cues such as colors and images can influence choices ( 52–55 ). There is also a recognition that other aspects of packaging design including auditory, haptic, and olfactory characteristics influence consumers ( 56 ) and that physical features (e.g., shape) influence attention in crowded marketplaces ( 56 , 57 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further research has examined the impact of food package graphic design on consumers, with these studies showing the utility of graphic design for being a useful tool in communicating consumer benefits ( 47 ), that the positioning of packaging elements influences consumer attention ( 48 ), and that a relationship between packaging design and willingness to pay exists ( 49 ). Additionally, food pack design research has shown that consumers are able to process multiple packaging messages concurrently ( 47 ), that visual design cues are an important influence on consumer choices ( 10 , 50 , 51 ), and that brand and other visual cues such as colors and images can influence choices ( 52–55 ). There is also a recognition that other aspects of packaging design including auditory, haptic, and olfactory characteristics influence consumers ( 56 ) and that physical features (e.g., shape) influence attention in crowded marketplaces ( 56 , 57 ).…”
Section: Introductionmentioning
confidence: 99%